How FEBS supports Young Scientists´ Careers - Díaz-Moreno, Irene; Kulda, Vlastimil; Jagusiak, Anna (Biologia Serbica, 2020)
The Federation of European Biochemical Societies (FEBS) brings together molecular life scientists in Europe and neighbouring regions. There are many activities of FEBS targeted to young scientists with the aim of promoting their careers. This article provides a brief overview of such FEBS initiatives.